Cover crops in a Wisconsin annual cropping system: Feasibility and yield effects. (22nd March 2022) - Malone, Lindsay Chamberlain; Mourtzinis, Spyridon; Gaska, John M.; Lauer, Joseph G.; Ruark, Matthew D.; Conley, Shawn P.
Abstract: Corn ( Zea mays L.), soybean [ Glycine max (L.) Merr.], and wheat ( Triticum aestivum L.) are important components of crop rotations in southern Wisconsin. Cover crops can protect soil and water in these systems. This study examines cover crop treatments in various crop sequences of these cash crops to determine effects on crop yield. Cover crops seeded following corn or soybean included cereal rye ( Secale cereale L.) or oat ( Avena sativa L.), which were either drilled after harvest, broadcast into the senescing crop, or drilled in alternating rows. Species planted after wheat included red clover ( Trifolium pretense L.) or berseem clover ( Trifolium alexandrinum L.), either frost seeded or drilled postharvest, as well as oat and rye drilled postwheat harvest in alternating rows. Broadcast seeding cereal rye preharvest into senescing soybean had the most successful establishment following corn or soybean. The system with the most consistent cover crop growth was winter‐hardy species established preharvest. However, this system decreased corn yield 5.8–8.6%. All other cover crop treatments had no effect on yield, but other postcorn or soybean treatments had limited growth. The highest yield for corn was observed following soybean, while soybean had the greatest yield when all three crops were present. Wheat yields were not affected by frost seeding or by rotation. This multiyear trial confirms the expected challenges of establishing cover crops in corn–soybean rotations in southern Wisconsin, while winter wheat provided clearer opportunities for cover cropping. Cover crop research in corn–soybean systems need to address the corn yield declines caused by cover crops. Core Ideas: Broadcast seeding cereal rye into soybean before harvest is a good option for southern Wisconsin. Cover crops did not affect soybean yield, while some cover crops did reduce corn yield. Frost seeding clover into winter wheat did not affect wheat grain yield.